Analisis Efektivitas Cooling Tower Sebelum dan Sesudah Pergantian Filler Pack - Mutiara Ghinaul Qalbi; Budi Suharto; Sri Wuryanti (Fakultas Teknik UMRI, 2024)
Cooling towers are components used to lower the temperature of condensate water from the condenser, which is pumped through the hot well pump. Given the importance of cooling towers as components used to lower condensate water temperature, the performance of these cooling towers must be maintained. One way to determine the effect of the filler pack is to conduct an analysis to determine the effectiveness parameters of the cooling tower. The analysis was conducted using the range approach and heat transfer methods. The results showed that the heat transfer effectiveness before replacing the filler pack was 68%, while after the replacement, the effectiveness increased to 72%. This indicates that replacing the filler pack has succeeded in increasing the effectiveness of the cooling tower.